KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DALAM MATERI HIMPUNAN DI KELAS VII - Emi Evriani; Yulis Jamiah; Hamdani Hamdani (UNIVERSITAS TANJUNGPURA, 2022)
This study aims to describe students' mathematical communication skills during the covid-19hpandemic in learning mathematics, especially set operations material. .The method used in this research is the descriptive method.. The research subjects in this study were students of SMP Negeri 2 Pontianak class VII G who had studied the set material. Collecting data in this study through tests,aand, interviews. Based on, the results of the study, it was ,found/ that ,the ability of /students to express mathematical ideas in online learning through writing on set operations material was 42.5% relatively low. Students tend not to be able to write set notation, students are also not able to describe Venn diagrams and students still have many errors in working on the given questions. The ability of students to describe mathematical ideas in online learning on set operations material is 55% low. Students tend to be able to describe Venn diagrams but are less clear and incomplete in describing Venn diagrams. The ability to explain students' mathematics in online learning through oral on set operations material is 65% classified as moderate. Students tend to be able to explain the steps of the answers they have done and give reasons for the answers well. The students' mathematical reading ability in online learning through oral on set operations material by 40% is low. Students havehnot been able to convey what is understood orally and haveknot been able to read mathematical notations anddterms.